Spiritual Letter-Travelogue in the Russian Monastic Literature of the 20 Century - A. N. Smolina (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The functioning of a travelogue letter in Russian monastic literature is considered on the material of the spiritual epistolary heritage of Archimandrite Sergius (Stragorodsky). Analyzing the work “In the Far East (Letters of the Japanese Missionary)”, the author shows the features of thematic and ideological content, the elocutive organization of spiritual epistolary texts combining the traits of letter and travelogue. The work reveals the linguistic stylistic features of spiritual travelogue: its lexical and figuratively tropetic characteristic is given. It is shown that in the analyzed texts stylistically marked linguistic elements are used: words and superword units related to the “Orthodoxy” thematic sphere. It is established that the naming of persons associated with Christian religious activities, the names of liturgical objects, the names of Orthodox holidays become a stylistic marker of spiritual letters- travelogues. The author focuses on the intertextual connections of the work “In the Far East ...”, reveals the New Testament and prayer intertextems that contribute to the actualization of Christian meanings. It is revealed in the article that the tropetic features of the works studied are due to the use of metaphors, epithets, religious allusions; figurative peculiarities are due to the use of enumeration, question-response, repetitions with religionisms components. It is concluded that spiritual travelogues fit into the context of Russian monastic literature - a unique and unexplored phenomenon of national culture.